2009
DOI: 10.1096/fj.08-121046
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Ets‐2 by oxidative stress induces Bcl‐xL expression and accounts for glial survival in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is an adult-onset neurodegenerative disease characterized by selective degeneration of motor neurons and glial activation. Cell-specific transcriptional regulation induced by oxidative stress may contribute to the survival and activation of astrocytes in the face of motor neuron death. In the present study, we demonstrate an age-dependent increase in Bcl-xL and Ets-2 immunoreactivity that correlates with an increase of glial fibrillary acidic protein (GFAP)-positive cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…Overexpression of TDP-43 Down-regulated Bcl-xL ExpressionEarlier studies have shown that Bcl-xL expression is reduced in motor neurons of mouse models of ALS and in human ALS cases (29,30). In accordance, Bcl-xL expression was reduced by overexpression of TDP-43 (Fig.…”
Section: Tdp-43-induced Death Is Associated With Increase Of Bim Exprmentioning
confidence: 56%
See 1 more Smart Citation
“…Overexpression of TDP-43 Down-regulated Bcl-xL ExpressionEarlier studies have shown that Bcl-xL expression is reduced in motor neurons of mouse models of ALS and in human ALS cases (29,30). In accordance, Bcl-xL expression was reduced by overexpression of TDP-43 (Fig.…”
Section: Tdp-43-induced Death Is Associated With Increase Of Bim Exprmentioning
confidence: 56%
“…Bcl-xL and Bcl-2 were reduced in brain areas where motor neuron death occurred in ALS model mice (29). Bcl-xL expression was found to be reduced in motor neurons of human ALS cases (30). These findings together suggest that the abnormal regulation of Bcl-2-related proteins may be responsible for the progression of motor neuron death in ALS.…”
Section: Tdp-43 Cleavage Leads To the Attenuation Of Tdp-43-inducedmentioning
confidence: 80%
“…In the majority of our cultures, GICs containing a downregulated NFkB pathway tend to differentiate toward a neuronal phenotype, which might reflect the need of NFkB-dependent survival factors by astrocytes. In line with this, Bcl-x L , an antiapoptotic NFkB target gene, contributes to the survival of primary astrocytes in culture (Lee et al, 2009), and it has been suggested that inhibition of the NFkB pathway blocks astroglial differentiation from mesencephalic neural precursors (Sabolek et al, 2006). However, tumor cells obtained from xenografted mice only showed a tendential, but not significant, pattern of neuronal differentiation after treatment with the NFkB activation inhibitor.…”
Section: Discussionmentioning
confidence: 95%
“…Our study shows that astrocyte survival is correlated with the elevation of Ets-2 transcription factor and with Bcl-xL expression [39]. The transcriptional activation of Bcl-xL by Ets-2 compensates oxidative stress by preventing astrocytes from apoptotic or necrotic cell death during the pathogenesis of ALS.…”
Section: How Are Astrocytes Adapted To Environmental Stresses and Whamentioning
confidence: 99%